Metalloporphyrin Complex‐Based Nanosonosensitizers for Deep‐Tissue Tumor Theranostics by Noninvasive Sonodynamic Therapy. Issue 5 (27th December 2018) - Ma, Aiqing; Chen, Huaqing; Cui, Yanhong; Luo, Zhenyu; Liang, Ruijing; Wu, Zhihao; Chen, Ze; Yin, Ting; Ni, Jun; Zheng, Mingbin; Cai, Lintao
Abstract: Metal complexes are widely used as anticancer drugs, while the severe side effects of traditional chemotherapy require new therapeutic modalities. Sonodynamic therapy (SDT) provides a significantly noninvasive ultrasound (US) treatment approach by activating sonosensitizers and initiating reactive oxygen species (ROS) to damage malignant tissues. In this work, three metal 4‐methylphenylporphyrin (TTP) complexes (MnTTP, ZnTTP, and TiOTTP) are synthesized and encapsulated with human serum albumin (HSA) to form novel nanosonosensitizers. These nanosonosensitizers generate abundant singlet oxygen ( 1 O2 ) under US irradiation, and importantly show excellent US‐activatable abilities with deep‐tissue depths up to 11 cm. Compared to ZnTTP‐HSA and TiOTTP‐HSA, MnTTP‐HSA exhibits the strongest ROS‐activatable behavior due to the lowest highest occupied molecular orbital−lowest unoccupied molecular orbital gap energy by density functional theory. It is also effective for deep‐tissue photoacoustic/magnetic resonance dual‐modal imaging to trace the accumulation of nanoparticles in tumors. Moreover, MnTTP‐HSA intriguingly achieves high SDT efficiency for simultaneously suppressing the growth of bilateral tumors away from ultrasound source in mice. This work develops a deep‐tissue imaging‐guided SDT strategy through well‐defined metalloporphyrin nanocomplexes and paves a new way for highly efficient noninvasive SDT treatments of malignant tumors. Abstract : Metalloporphyrin complexes (MnTTP, TiOTTP, and ZnTTP) are synthesized and encapsulated with human serum albumin (MTTP‐HSA). They show good 1 O2 generation in mimic tissues even up to 11 cm away from the ultrasound source, and MnTTP‐HSA exhibits the best sonodynamic behavior. Guided by photoacoustic/magnetic resonance imaging, MnTTP‐HSA achieves high sonodynamic efficiency by completely suppressing the distant tumor growth in vivo.